The Self-Concept of Students Receiving Bidik Misi Scholarships at University of Jember - Garniasih, Belly; Jannah, Raudlatul (Jurnal ENTITAS SOSIOLOGI, 2018)
One of the scholarship programs at the University of Jember, which annually provides a lot of quotas, is a scholarship through the Bidikmisi program, which is given to students who come from economically low-income families and a good history of achievement. As it is known that ideally, Bidikmisi students must behave, appear, and act according to the definition of Bidikmisi scholarship itself to prevent misunderstandings in the use of scholarship funds. But still, some Bidikmisi students at Jember University do not display the definition of 'ideal.' From this phenomenon, a question arises about 'Self-Concept of Bidikmisi Students at Jember University.' In this study, researchers used a qualitative descriptive approach, which aims to obtain information about the self-concepts of Bidikmisi students at Jember University. The theory used is symbolic interactionism by George Herbert Mead, where the theory explains that a person is seen as an actor who interprets, evaluates, defines, acts, and tells about the use of symbols as a form of interpretation in one's interactions with others or with groups. The symbols used cold become in the form of verbal or nonverbal. The results showed that there were two kinds of Bidikmisi students' self-concepts, namely positive concepts and negative concepts. Positive self-concept, namely (1) making parents proud, (2) getting high achievements and aspirations, (3) being responsible. On the other hand, negative self-concepts are (1) feeling inferior (2) overly confident. Keywords: self-concept, Bidikmisi students, positive concepts, negative concept Referensi: Burns, R.B. 1993. Konsep Diri Teori, Pengakuan, Perkembangan dan Perilaku. Jakarta. Arcan. Alih bahasa: Eddy. belmawa.ristekdikti.go.id/petunjuk/pedoman&ved (diakses pada 10/03/2018). Rakhmat, Jalaludin. 2007. Psikologi Komunikasi. Bandung: PT Remaja Rosdakarya. Ritzer dan Goodman. 2012. Teori Sosiologi Dari Teori Sosiologi Klasik Sampai Perkembangan Mutakhir Teori Sosial Postmodern. Bantul: Kreasi Wacana. Sobur, Alex. 2013. Psikologi Umum dalam Lintasan Sejarah. Bandung: Pustaka Setia. Shintaviana, Fransisca Vivi. 2014. Konsep Diri Serta Faktor-Faktor Pembentuk Konsep Diri Berdasarkan Teori Interaksionisme Simbolik (Studi Kasus Pada Karyawan Kantor Kamahasiswaan, Alumni Dan Campus Ministry Universitas Atma Jaya Yogyakarta. Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Atma Jaya Yogyakarta. E-journal.uajy.ac.id.id/5780/ (diakses pada 17/09/2017).